IDENTIFIKASI FAKTOR–FAKTOR PENYEBAB ALIH FUNGSI LAHAN SAWAH MENJADI NON SAWAH DI KECAMATAN TOMPASOBARU KABUPATEN MINAHASA SELATAN - Rendy Christian Laoh; Theodora M. Katiandagho; Celsius ., Talumingan (Sam Ratulangi University, 2018)
This study aims to identify factors causing the conversion of wetland to non-rice field in Tompaso Baru Sub-district of South Minahasa Regency. This research was conducted for 3 months from December 2017 until January 2018. The data used in this research are primary data and secondary data. Primary data was optained from interview to respondent, while secondary data was optained from Tompaso Baru District office and BP4K. The result of the research shows the factors causing the conversion of rice field in Tompaso Baru sub-district of South Minahasa Regency are economic factors (low farm income, land selling price), policy, and availability of water.*ghmk*.